A unique mapping strategy for localization and ablation of the atrial input of an antegrade only conducting accessory pathway. (4th March 2021) - Ward, Chad; Kamp, Anna; Kertesz, Naomi; Kalbfleisch, Steven
Abstract: The standard technique for accessory pathway ablation involves mapping along the mitral and tricuspid annulus to localize the regions of earliest ventricular activation during antegrade pathway conduction, earliest atrial activation during retrograde conduction or detection of an accessory pathway potential. In some cases despite what appears to be appropriate mapping, catheter positioning and adequate power delivery the ablation is not successful. In many of these cases, the pathway is felt to be inaccessible because of a location remote from the mitral or tricuspid annulus that cannot be affected by endocardial power delivery along the annulus. In the case of difficult left sided pathways, some may be reached and ablated via the coronary sinus or its branches. Right sided pathways cannot be approached in this fashion since there is no venous structure analogous to the coronary sinus around the tricuspid annulus. Alternative mapping and ablation techniques for these difficult pathways have included epicardial mapping via direct pericardial access or attempts to localize pathway insertion areas remote from the valve annulus which may be amenable to endocardial ablation. We describe the use of post‐pacing interval mapping to localize the atrial input of a right sided antegrade only accessory pathway that was resistant to conventional mapping and ablation strategies.